2022
DOI: 10.1111/cid.13131
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of implant supported mandibular overdentures with cantilever bar and stud attachments: A retrospective study

Abstract: Background Treatment of edentulous patients with implant‐supported over‐dentures improves denture's retention and stability. Published data concerning implant‐supported overdenture with cantilever bars that claimed that can affect the survival and bone loss of implants are scarce. Purpose The purpose of this study was to evaluate 5‐year clinical performance of mandibular implant‐supported over‐dentures with different attachment systems. Materials and methods In this retrospective study, 103 patients who had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Subsequently, the development of favorable masticatory performance took place in both groups, however, group II was superior to group I in this study. Such a finding coincides with other investigations mentioning the fact that the degree of muscle activity mainly relies on the nature of prosthetic support, stability, and retention [ 20 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Subsequently, the development of favorable masticatory performance took place in both groups, however, group II was superior to group I in this study. Such a finding coincides with other investigations mentioning the fact that the degree of muscle activity mainly relies on the nature of prosthetic support, stability, and retention [ 20 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Improvement was achieved through reduced functional complaints, improved appearance, and reduced functional limitations. The implant-supported prosthesis also reduced inappropriate jaw alignment, physical, and psychological disabilities [ 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the subgroup analysis of the IOD studies in terms of the attachment type suggests that there is no difference between bar‐ or single attachment‐retained/supported IODs. The evidence regarding the effect of the attachment type on dPROs had not been clearly established (Kuoppala et al, 2013; Nejatidanesh et al, 2022). In general, studies have shown that patients are least satisfied with magnet‐retained IODs, but no general superiority of bars over single attachments has yet been demonstrated (Cune et al, 2005; Kim et al, 2012), supporting the result of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the subgroup analysis of the IOD studies in terms of the attachment type suggests that there is no difference between bar-or single attachment-retained/supported IODs. The evidence regarding the effect of the attachment type on dPROs had not been clearly established (Kuoppala et al, 2013;Nejatidanesh et al, 2022). In has a positive effect on dPROs Policastro et al, 2019;Schwindling et al, 2018).…”
Section: Subgroup Analyses In Implant Overdenture Groupsmentioning
confidence: 97%